Efficacy of the Young Women's CoOp: An HIV Risk-Reduction Intervention for Substance-Using African-American Female Adolescents in the South. Issue 3 (4th May 2017) - Wechsberg, Wendee M.; Browne, Felicia A.; Zule, William A.; Novak, Scott P.; Doherty, Irene A.; Kline, Tracy L.; Carry, Monique G.; Raiford, Jerris L.; Herbst, Jeffrey H.
ABSTRACT: HIV/sexually transmitted infection (STI) risk-reduction interventions are needed to address the complex risk behaviors among African-American female adolescents in disadvantaged communities in North Carolina. In a two-group randomized trial, we reached 237 sexually active, substance-using African-American female adolescents, to test a risk-reduction intervention, the Young Women's CoOp (YWC), relative to a nutrition control. In efficacy analyses adjusting for baseline condom use, at three-month follow-up participants in the YWC were significantly less likely to report sex without a condom at last sex relative to control. There were mixed findings for within-group differences over follow-up, underscoring the challenges for intervening with substance-using female youths.